Development of an Intelligent Communication Platform for Remote Practical Work in Education: Integrating AR, VR, and Cloud Technologies - El Gourari Abdelali; Ezzini Mustapha; Raoufi Mustapha; Skouri Mohammed; Achki Samira; Ait Lahcen Yassine; Mouachi Raja (ITM Web of Conferences)
This paper presents the development of an intelligent communication platform designed for Remote Practical Works (RPWs) in educational settings. The platform addresses the increasing need for accessible and participatory practical learning solutions in the context of distance education. By utilizing augmented reality (AR), virtual reality (VR), cloud computing, and machine learning, it bridges the gap between theoretical knowledge and hands-on application to enhance student engagement and learning outcomes. Key features include real-time collaboration, personalized learning experiences, and seamless access to virtual labs, all supported by robust cybersecurity measures and scalable infrastructure. The platform integrates with existing learning management systems (LMS) to provide a flexible and secure learning environment. A systematic development process, guided by user feedback, ensures continuous improvement and alignment with educational goals.